Optimizing Public Services Through Reforming State Apparatus Resources: A Public Policy Analysis - Ach Ilyasi (Universitas Muhammadiyah Jember Press, 2024)
This research aims to answer the main question about how optimization of public services can be achieved through resource reform of the state apparatus. This research was carried out over six months, from January to June 2024, with data collection through documentation studies, in-depth interviews, surveys, and participant observation. Data were analyzed using qualitative analysis techniques with the help of NVivo software. The research results show that although the government's policy on reforming state apparatus resources is theoretically excellent and constructive, implementation in the field often needs to be revised. The main obstacles are low professionalism, integrity, work ethics, and lack of responsibility for public needs. To overcome these obstacles, this research recommends increasing training and capacity development, strengthening codes of ethics, using information technology, and improving a more adaptive and innovative work culture. Implementing these suggestions can increase efficiency, transparency, and accountability in Indonesia's public services, meet public expectations, and create a more effective government.